Proton Irradiation Effect on InP‐Based High Electron Mobility Transistor by Numerical Simulation with Non‐Uniform Induced Acceptor‐Like Defects. Issue 6 (18th April 2018) - Sun, Shuxiang; Chang, Mingming; Zhang, Chao; Cheng, Chao; Li, Yuxiao; Zhong, Yinghui; Ding, Peng; Jin, Zhi; Wei, Zhichao
Abstract : In this paper, an improved charge control model is proposed to investigate the effect of proton irradiation on InP‐based high electron mobility transistor (HEMT) with fluence varying among 0, 1 × 10 11, 5 × 10 11, 1 × 10 12, and 2 × 10 12  cm −2 . The non‐uniform acceptor‐like defects in InAlAs/InGaAs hetero‐junction layers have been taken into account in the charge control model of the device after proton irradiation. The simulated characteristics by the charge control model have shown compatible trend with experimental data. The calculated results show that the channel current, transconductance, and current gain cutoff frequency depict a decline trend with the increase of proton fluence, and the pinch‐off voltage drifts toward positive value. Moreover, the performances gradually begin to degrade after the proton fluence reaches 5 × 10 11  cm −2, and deteriorate dramatically with proton fluence up to 2 × 10 12  cm −2 . The observed obvious variation of electrical properties with different proton fluence could be accounted for by the carrier sheet density reduction, which is a result of the carrier removal effect from induced As acceptor‐like defects. Abstract : Proton irradiation effect on InP‐based high electron mobility transistors (HEMTs) is investigated by charge control analytical model with induced As acceptor‐like defects distributing non‐uniformly in hetero‐junction layers. The channel current, transconductance, and current gain cutoff frequency depict a decline trend with proton fluence, and the pinch‐off voltage drifts toward positive value. The obvious deterioration of electrical properties is due to the 2DEG reduction.